Effectiveness of influenza vaccination in preventing confirmed influenza cases and hospitalizations in Northern Spain, 2023/24 season: A population-based test-negative case-control study - Iván Martínez-Baz; Ana Navascués; Camino Trobajo-Sanmartín; Francisco Pozo; Miguel Fernández-Huerta; Maddi Olazabal-Arruiz; Lucía Argente-Colas; Guillermo Ezpeleta; Aitziber Echeverria; Itziar Casado; Carmen Ezpeleta; Jesús Castilla (International Journal of Infectious Diseases)
Objective: We estimated the influenza vaccination effectiveness (IVE) in preventing medical consultations and hospitalizations due to influenza during the 2023/24 season. Methods: Two test-negative case-control studies analyzed patients who consulted primary healthcare or were hospitalized for respiratory symptoms and were tested for influenza by PCR in the 2023/24 season in Navarre, Spain. Influenza vaccination status in the current and previous seasons was compared between confirmed influenza cases and test-negative controls. IVE was calculated as (1-adjusted odds ratio)×100. Results: Of 3133 hospitalized patients, 529 (17%) were positive for influenza: 71% A/H1N1, 23% A/H3N2, and 7% A nonsubtyped. IVE to prevent hospitalizations was 43% (95%CI: 26%, 56%) overall, 61% (95%CI: 32%, 77%) in people younger than 65 years old and 35% (95%CI: 10%, 53%) in older people. IVE was 48% (95%CI: 30%, 61%) against influenza A/H1N1, and 15% (95%CI: -42%, 49%) against influenza A/H3N2. IVE in people vaccinated only in the previous season was 28% (95%CI: -5%, 51%). Among 417 outpatients, 146 (35%) were confirmed for influenza. IVE to prevent outpatient cases was 49% (95%CI: -9%, 76%) overall and 42% (95%CI: -33%, 74%) against influenza A/H1N1. Conclusions: IVE was moderate against influenza A/H1N1 and low against influenza A/H3N2 in the 2023/24 season.